The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1983
DOI: 10.1126/science.221.4607.221
|View full text |Cite|
|
Sign up to set email alerts
|

Sulfur Diagenesis in Everglades Peat and Origin of Pyrite in Coal

Abstract: The pattern of sulfur transformation in peat across the Everglades basin indicates that pyrite formation in organic-rich swamps depends on the use of organic oxysulfur compounds in dissimilatory respiration by sulfur-reducing bacteria. This paragenesis explains the primary distribution of sulfur compounds in low-sulfur coals and possibly in most coals and many organic-rich soils and sediments. It also accounts for the occurrence of framboidal pyrite bound in fossil tissue in coal and sediments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
55
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(61 citation statements)
references
References 41 publications
6
55
0
Order By: Relevance
“…Although the analytical methods used by Altschuler et al (1983) were substantially different from ours, many of the methods used by Casagrande et al ( 1977) were similar. Casagrande et al removed SOa2--S (using 0.1 M LiCl) and SO-S (using CHC13) before dividing their samples and subjecting one subsample to HI reduction and another subsample to the Zn-HCl procedure.…”
Section: Biogeochemical Transformationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the analytical methods used by Altschuler et al (1983) were substantially different from ours, many of the methods used by Casagrande et al ( 1977) were similar. Casagrande et al removed SOa2--S (using 0.1 M LiCl) and SO-S (using CHC13) before dividing their samples and subjecting one subsample to HI reduction and another subsample to the Zn-HCl procedure.…”
Section: Biogeochemical Transformationsmentioning
confidence: 99%
“…Values are means + SE. For comparison, data are also shown for freshwater peat from the Okefenokee Swamp (Casagrande et al 1977; values are the means of the Minnie's Lake and Chesser Prairie sites) and from the Florida Everglades (Altschuler et al 1983; values are the means of core 2, 20-25 cm, and core 8, 14-19 cm). of S from all of the inorganic S compounds except So (68% recovery) and FeS, (2% recovery).…”
Section: Biogeochemical Transformationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitchell et al (198 1,1984) have shown that organic S usually constituted >80% of the total S in the sediments of three New York lakes. King and Klug (1982) found in hypereutrophic Wintergreen Lake sediments, where low redox conditions and high carbon levels would seem to favor pyrite formation, that organic S was still >80% of total S and that pyrite was < 10% oftotal S. Altschuler et al (1983) found organic S predominant in peat deposits across the Everglades basin and indicated that pyritic S formation in this reduced substrate was dependent on the use of organic S compounds in dissimilatory respiration by S-reducing bacteria. Mitchell et al (1984) and Landers and Mitchell (unpubl.…”
mentioning
confidence: 99%